The loser's long curse: Electoral consequences of a class conflict - Jaakko Meriläinen; Matti Mitrunen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper presents evidence of political legacies of exposure to a violent class conflict over 100 years. We revisit the Finnish Civil War of 1918 and first trace out the impact of local conflict exposure on electoral outcomes over a quarter-century period between the World Wars. The electoral performance of left-wing parties that backed the insurgents was persistently and negatively affected by civil war casualties on both sides of the conflict. Our evidence suggests that this effect can be attributed to at least three mechanisms: a mechanical effect of party supporters perishing in the civil war, a backlash against the losing side, and voters reacting to post-civil war concessions and reforms that most impacted war-affected municipalities. We also show that the civil war had a persistent impact on the Finnish electoral politics: left-wing parties have been less popular in conflict-hit municipalities even in modern-day elections.
Keywords: D72; D74; N94; O12; 330; civil war; class conflict; electoral politics; impact persistence; left-wing parties